2010
DOI: 10.1164/rccm.200909-1350oc
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mycotoxins Increases the Allergic Immune Response in a Murine Asthma Model

Abstract: Our results demonstrate that gliotoxin and patulin increase the allergic immune response in mice by modulating the Th1/Th2 balance via direct effects on IL-12 secretion in DCs and by inducing oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 52 publications
3
64
1
1
Order By: Relevance
“…First, the role of SDC4 in allergic asthma was investigated by comparing SDC4 À / À versus wild-type (WT) mice in a murine asthma model [15][16][17] . Histological analysis of haematoxylin and eosin (H&E)-stained lung sections showed less inflammatory infiltrates in the airways of OVA-immunized SDC4 À / À mice compared with WT animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the role of SDC4 in allergic asthma was investigated by comparing SDC4 À / À versus wild-type (WT) mice in a murine asthma model [15][16][17] . Histological analysis of haematoxylin and eosin (H&E)-stained lung sections showed less inflammatory infiltrates in the airways of OVA-immunized SDC4 À / À mice compared with WT animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Left lung was fixed in 10% formalin and stained with H&E (MERCK, Darmstadt, Germany). For objective evaluation and quantification of the degree of pulmonary inflammation, lung sections were scanned with a digital camera (Visitron systems, USA, five shots per lung) and analysed with HistoClick-Software based on morphometric image analysis developed in our laboratory 15,16 . The degree of inflammation is expressed as the number of pixels that correlate to the stained cells of interest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 395 subjects with asthma, they found that high mold exposure significantly modified the relation between three SNPs in CHIT1 and severe exacerbations requiring emergency department visits. In a related article, Schü tze and colleagues sought to determine whether and how mycotoxins, secondary metabolites of mold, might exacerbate asthma (57). They found that the administration of mycotoxins to the lung or colon enhanced the severity of the asthma-like phenotype of mice after ovalbumin sensitization and challenge.…”
Section: Occupational and Environmental Asthmamentioning
confidence: 99%